2021
DOI: 10.1093/jpe/rtab076
|View full text |Cite
|
Sign up to set email alerts
|

Chilling rather than photoperiod controls budburst for gymnosperm species in subtropical China

Abstract: Aims The mechanisms regulating spring phenology have been extensively studied in angiosperm species. However, given that gymnosperms and angiosperms diverged 300 million years ago, phenology may be triggered by different cues in gymnosperm species. The regulatory mechanisms of phenology in subtropical regions remain largely unknown. In combination, it remains untested whether subtropical gymnosperm species have chilling requirements and are photosensitive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…Our experimental findings confirm that seedlings of the subtropical pecan grown in southeastern China also evince these traits. This is in line with recent studies, which show that several subtropical tree species have a rest period and a chilling requirement ( Du et al, 2019 ; Song et al, 2020 ; Pan et al, 2021 ; Zhang et al, 2021a , b ). The novelty and scarcity of these findings in the case of subtropical trees are in striking contrast with the case of boreal and temperate trees, where the existence of these traits has already been known for a 100 years ( Coville, 1920 ; Jewaria et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our experimental findings confirm that seedlings of the subtropical pecan grown in southeastern China also evince these traits. This is in line with recent studies, which show that several subtropical tree species have a rest period and a chilling requirement ( Du et al, 2019 ; Song et al, 2020 ; Pan et al, 2021 ; Zhang et al, 2021a , b ). The novelty and scarcity of these findings in the case of subtropical trees are in striking contrast with the case of boreal and temperate trees, where the existence of these traits has already been known for a 100 years ( Coville, 1920 ; Jewaria et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…For the structure of the overall model, refer to Supplementary Figure 1. (Du et al, 2019;Song et al, 2020;Pan et al, 2021;Zhang et al, 2021a,b). The novelty and scarcity of these findings in the case of subtropical trees are in striking contrast with the case of boreal and temperate trees, where the existence of these traits has already been known for a 100 years (Coville, 1920;Jewaria et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found a decreased WT and a slightly increased ST below 500 m in the QB from 2001 to 2011, which somewhat provides more sufficient accumulation of chilling and forcing for the onset of spring phenology (Fu et al, 2015a;Ettinger et al, 2020;Pan et al, 2022). However, the SOS in this region was delayed (Figure 4D).…”
Section: Sos Response To Driving Factorssupporting
confidence: 48%
“…The daylength effect is species-specific ( Basler and Körner, 2012 ; Zohner and Renner, 2015 ), and previous experimental studies found a wide range of responses from being insensitive to daylength to showing no budburst at all under short days ( Zohner and Renner, 2015 ; Zohner et al, 2016 ). These studies mostly focused on inter-specific comparisons within angiosperms, while population-level studies that also involve gymnosperms are scarce (but see Kumar and Sati, 2016 ; Pan et al, 2021 ; Wu et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%